Synthesis and characterization of hybrid organic coating system to reduce thermal degradation of solar cells / Farah Khaleda Mohd Zaini - Farah Khaleda , Mohd Zaini (2020)
Thermal-decreasing hybrid organic coatings were developed for crystalline solar cells by using two types of binder systems; namely Aminopropyltriethoxysolution (APTES) / Methyltrimethoxysilane (MTMS) binder system (labelled as B1) and Methyltrimethoxysilane (MTMS) / nitric acid (HNO3) binder system (labelled as B2). Three types of nanoparticles; Titanium dioxide, TiO2 (Anatase), Zinc oxide, ZnO and Tin dioxide, SnO2 nanoparticles with different weight percentage were introduced inside each binder system namely; 20 wt%, TiO2 (T1B1 coating), 60 wt% TiO2 (T2B1 coating), 20 wt% ZnO (Z1B1 coating), 60 wt% ZnO (T2B1 coating), 20 wt% SnO2 (S1B1 coating) and 60 wt% SnO2 (S2B1 coating) for B1 binder system and 20 wt%, TiO2 (T1B2 coating), 60 wt% TiO2 (T2B2 coating), 20 wt% ZnO (Z1B2 coating), 60 wt% ZnO (Z2B2 coating), 20 wt% SnO2 (S1B2 coating) and 60 wt% SnO2 (S2B2 coating) for B2 binder system. This work highlights the effects of nanoparticle coating systems on the surface temperature of solar cells along with several structural and electrical studies. It is found that B1 coating systems showed a better performance in decreasing the surface temperature of solar cells compared to B2 coating systems. The introduction of nanoparticles inside the binder systems further reduced the surface temperature of solar cells from 55.75 °C (non-coated solar cell) at 60th minute of exposure under standard test condition (STD) of 1000 W/m2 irradiation and room temperature of 25°C. Under the same condition, S1B1 nanoparticle coating records the lowest temperature of 42.66°C for B1 binder system and Z1B2 coating system records a reduced temperature of 48.82°C for B2 binder system. Furthermore, the fill factor of solar cells was also improved by approximately 0.1 or 16.67% with binder coating systems (B1 and B2 coating systems) and about 0.2 or 33.33% with nanoparticle coating systems (T1B1, T2B1, Z1B1, T2B1, S1B1, S2B1, T1B2, T2B2, Z1B2, Z2B2, S1B2, S2B2 coating systems).